Developmental Analysis of the Human Development Index Regencies and Cities in East Nusa Tenggara Province Period 2015-2021 - Amalo, Fitriningsih (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this research is to know the development of HDI seen from the 3 elements of Education, Health and income of the Regency/City throughout the Province of NTT for the period 2016-2022. The method used is descriptive statistics. The results of this study indicate that the HDI level of Kupang City from the three elements reaches a number that exceeds the national target in the expectation of length of schooling, per capita expenditure also dominates the city of Kupang at Rp. 13,000 in which other districts, namely sabu Raijua only Rp. 5,000., and the average age of death for other counties is around 60 years.